Studies Effectiveness System Management Operational For Optimization Costs in Industry Hospitality - Ridzky, Muhammad Maulana (Hospitality Management and Operations Journal, 2024)
Industry hospitality face challenge significant in manage cost operational consequence pressure competition and improvement price . Effectiveness system management good operational? become important For help hotels maintain Power competition without sacrifice quality services . Research This aiming For evaluate effectiveness system management operational in optimize costs in several starred hotels in Indonesia, especially through management power work , energy , and food and beverages . Research This use approach quantitative with method descriptive-analytical . Data obtained of the 50 hotels that have implement system management based on technology . Instruments study covering questionnaire and interview structured analyzed? use statistics descriptive and regression multiple For identify influence system management to subtraction costs . Research results show that automation and usage technology in management power Work succeed reduce cost up to 15%, while implementation system management energy can reduce cost utilities up to 20%. In addition that , the implementation management inventory data based reduce waste food up to 30%, which has an impact positive on efficiency cost operational . Conclusion from study This is that system management operational based on technology proven effective in optimize costs , and results This offer guide for hotel manager for increase efficiency operational in a way overall .